Hijacking gene regulation in Saccharomyces cerevisae Utilization of the transcription terminating protein complex Nrd1-Nab3-Sen1 - Widén, Tove (My University, 2019)
The Nrd1-Nab3-Sen1 (NNS) complex in Saccharomyces cerevisiae is essential for its role in terminating transcription for non-coding RNAs. However, it also regulates gene expression for some protein coding genes by prematurely terminate transcription through simultaneous binding of the nascent transcript and the RNA Polymerase II. In this thesis I investigate the effect the NNS complex have on expression and study how the RNA binding sites recognized by Nrd1 and Nab3 can be utilized to regulate expression. I confirm that the NNS complex reduces the expression and extrisic noise between cells of the native NNS target Pic2. I also show that short DNA sequences containing NNS binding sites can be placed between the promoter and a gene in order to fine tune its expression. In addition I create an anchor away system inducible by the plant hormone abscisic acid. It enables export of a nuclear protein to the cytoplasm and can be used to study the function of essential nuclear proteins that cannot be knocked out.
Keywords: Biokemi och molekylärbiologi; Cellbiologi; Medicinsk bioteknologi (med inriktning mot cellbiologi); Livsvetenskaper; Biochemistry and Molecular Biology; Cell Biology; Medical Biotechnology (with a focus on Cell Biology); Life Science